Etnobotani Tumbuhan Upacara Adat Etnis Ngadha di Kecamatan Jerebu’u Kabupaten Ngada, Propinsi Nusa Tenggara Timur - Mariana Sada; Jumari Jumari (Saintek Lahan Kering, 2018)
Ethnic Ngadha is one of the largest traditional communities in Ngada District. In the middle of globalization and modernity, their lives are still held in the tradition which is a heritage from their ancestors. One of a special characteristic of this tradition is the ceremonies in their community. This research has been done in February to May 2016 at Tiwuriwu, Watumanu and Dariwali villages, Jerebu’u Sub-District, District of Ngada. The aims of this research were to inventories the species of the plant, to investigate their meaning in each ceremony and conservation efforts undertaken by the community. The methods were used to collect the data was exploratory, participant observation and interviews. Based on this research, we found 60 of plants species including 26 families were used in ceremonies of ethnic Ngadha. The Poaceae is the most used family in their ceremonies with 15 species, Fabaceae with 8 species, Arecaceae with 6 species, Musaceae and Solanaceae each of them 3 species, while other families between 1 or 2 species. Each type of species has a specific meaning in any ceremonies in accordance with the intent and purpose of the ceremony. The efforts to conserve these plants have been done by local people by cultivation the plants around their yard, garden or field.